Targeting Bone Metastases Signaling Pathway Using Moringa oleifera Seed Nutri-miRs: A Cross Kingdom Approach. (30th June 2022) - Bhadresha, Kinjal; Patel, Maulikkumar; Brahmbhatt, Jpan; Jain, Nayan; Rawal, Rakesh
Abstract: Moringa oleifera is a medicinally important plant that has various medical and nutritional uses. Plant miRNAs are a class of non-coding endogenous small RNAs that regulate human-specific mRNA but the mechanistic actions are largely unknown. Here, in this study, we aim to explore the mechanistic action and influence of M. oleifera seed miRNAs on vital human target genes using computer based approaches. The M. oleifera seed miRNAs sequence was taken from published data and identified its human gene targets using a psRNA target analysis server. We identified 94 miRNAs that are able to significantly regulate 47 human target genes, which has enormous biological and functional importance. Out of 47 human targeted genes, 23 genes were found to be associated with PI3K-AKT, RUNX, and MAPK1/MAPK3 signaling pathway which has shown to play key roles in bone metastases during cancer progression. The M. oleifera seed miRNAs hold a strong potential for future research that might uncover the possibility of miRNA-facilitated cross-kingdom regulation and therapeutic targets for bone metastases.